STUDI KERUANGAN DAN KELEMBAGAAN PENGELOLAAN EKOWISATA MANGROVE DI NEGERI AMAHAI, KABUPATEN MALUKU TENGAH - Reyaan, Yosep M; Abrahamsz, James; Asikin, Erawan (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2025)
Ecotourism is a tourist activity that aims to conserve. In its implementation, institutions have a very important role for sustainable ecotourism management. This study aims to determine the forms of space utilization in mangrove ecotourism, analyze the suitability and carrying capacity of ecotourism areas, analyze the role of institutions in influencing the success of ecotourism management, and formulate a strategy for managing ecotourism in Negeri Amahai. The research was conducted in Negeri Amahai, Central Maluku Regency in January-May 2023. Mangrove data were collected by purposive sampling using transect lines. Analysis of land suitability and carrying capacity using established formulas. Management strategies using SWOT and TOWS with policy priorities further analyzed with AHP. The results showed, the tourist space in mangrove ecotourism is in the form of reception space, service space and tourist space. There are various forms of utilization in the space both supporting ecotourism activities such as educational facilities, trade, trash bins, sanitation and communication, and there are still activities that threaten such as mangrove logging and sand mining. The suitability of mangrove ecotourism at station I is categorized as “Very Suitable” with IKW 85%, while at station II as “Suitable” with IKW 64%. The carrying capacity of mangrove ecotourism area can accommodate 31 tourists/day. The role of institutions in the management of mangrove ecotourism is considered “Not Optimal” because it does not yet have institutions or rules that focus on management of mangrove ecotourism. There are 11 strategies and 5 priorities in managing mangrove ecotourism in Negeri Amahai. ABSTRAK Ekowisata merupakan suatu kegiatan wisata yang bertujuan untuk konservasi. Dalam pelaksanaanya, kelembagaan memiliki peran yang sangat penting untuk pengelolaan ekowisata berkelanjutan. Penelitian ini bertujuan untuk mengetahui bentuk-bentuk pemanfaatan ruang pada ekowisata mangrove, menganalisis kesesuaian dan daya dukung kawasan ekowisata, menganalisis peran kelembagaan dalam mempengaruhi keberhasilan pengelolaan ekowisata, dan memformulasikan strategi pengelolaan ekowisata Negeri Amahai. Penelitian dilakukan di Negeri Amahai, Kabupaten Maluku Tengah pada Januari-Mei 2023. Pengambilan data mangrove secara purposive sampling dengan menggunakan garis transek. Analisis kesesuaian lahan dan daya dukung menggunakan rumus yang ditetapkan. Strategi pengelolaan menggunakan SWOT dan TOWS dengan prioritas kebijakan dianalisis lebih lanjut dengan AHP. Hasil penelitian menunjukan bahwa ruang wisata pada ekowisata mangrove berupa ruang penerimaan, ruang pelayanan dan ruang wisata. Terdapat beragam bentuk pemanfaatan pada ruang tersebut baik yang mendukung kegiatan ekowisata seperti fasilitas edukasi, perdagangan, tempat sampah, sanitasi dan komunikasi, serta aktivitas yang mengancam seperti penebangan mangrove dan penambangan pasir. Kesesuaian ekowisata mangrove pada stasiun I dikategorikan “Sangat Sesuai” dengan IKW 85%, sedangkan pada stasiun II dikategorikan “Sesuai” dengan IKW 64%. Daya dukung kawasan ekowisata mangrove Negeri Amahai mampu menampung 31 wisatawan/hari. Peran kelembagaan dalam pengelolaan ekowisata mangrove Negeri Amahai dinilai “Belum Optimal” dikarenakan belum memiliki lembaga maupun aturan yang fokus pada pengelolaan ekowisata mangrove. Terdapat 11 strategi dan 5 prioritas dalam pengelolaan ekowisata mangrove Negeri Amahai. Kata Kunci: Ekowisata, mangrove, kesesuaian, daya dukung, kelembagaan